Marcadores moleculares associados ao infarto agudo do miocárdio - Inácio, Juarez (1998)
In recent years, cardiovascular diseases have become the most important cause of' death in Brazil. The success in treatments of infarcted patíents through inhibitors of the kngiotensin-Converting Enzyme (ACE) stimulated studies toward the investigation of existing polymorphisms on the ACE gene and its association to myocardium infarction (MI). However, the renin-angiotensin System (RAS) is an important regulatory pathway of the ACE. Therefore, other important genes involved ín this system may also present polymorphisms that could affect 41 occurence. An example could be the ATI and AT2 receptors, vbich intermediate vasoconstriction actions of the RAS, íecoming candidate genes associated to MI and hypertension. 7his research aimed to investigate the possible association of :he ACE and the ATI receptor gene polymorphism with the acute lyocardium infarction (AMI) • Genotypic and allelic freguencies >f the brazilian population were also determined for the ACE iene. The investigstion of possible mutation in the intron 16 >f the ACE gene was also done through the PCR-LIS-SSCP (low ionic strength-single stranded conformational polymorphism) technique. Correlation between ACE and ATI receptor was highly significant. However, the high and significant canonical correlation (0.73; p<0,01) between non-favorable alelles for both genes (D and C) and a more intense acute myocardium infarction demonstrated that there is a synergistic effect of both polymorphisms. When non-favorable alelles were considered individually, they had a correlation coefficient of 0.58 (p<0 05) This result suggests that patients with both mutations have a 50% higher chance of an AMI. Comparison of the alellic and genotypic frequencies of the ACE gene polymorphism between a group of infarcted patients and the brazilian population did not reveal differences, with a frequency of 0.61 for the D alelle. The higher frequency of the non-favorable alelle and the similar genotypic frequencies for infarcted patients and the brazilian population, may suggest that this risk factor associated to other factors may predispose the majority of the regulation to a more intense AMI. Mutational analysis through LIS-SSCP in the intron 16 of the ACE gene in 80 individuais did not detect any different conformation. The association among ACE, ATI receptor and AMI can be used as a powerful diagnostic tool for AMI prevention. Other markers must be investigated to increase the power of the test in order to prevent or even to change life habits, consequently avoiding death or extending life span.